Pengaruh Penggunaan Media Pembelajaran Manipulatif Terhadap Motivasi Belajar Siswa Kelas 5 SDN 3 Gunungsari Tahun Pelajaran 2020/2021 - Sari, Dian Purnama; Karma, I Nyoman; Tahir, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
This study aims to determine the effect of using manipulative learning media on the learning motivation of 5th graders at SDN 3 Gunngsari in the 2020/2021 school year. This research is motivated by the use of manipulative learning media in increasing students' learning motivation. Data collection methods used are Observation, Documentation, and Questionnaire. The data analysis technique used is descriptive analysis technique and inferential analysis technique. Descriptive data analysis technique is distribution, while inferential analysis technique is using Test (t) , and Sie Effect. The results of the normality test showed that the data was normally distributed, and the results of the homogeneity test obtained homogeneous data, while the results of the Hypothesis Test showed that there was a significant influence on the use of manipulative learning media on the learning motivation of 5th grade students at SDN 3 Gunungsari in the 2020/2021 academic year. This can be seen from the results of observations of the implementation of the use of manipulative learning media in the experimental group, namely in the first treatment a total score of 77.5 with good criteria, while in the second treatment the total score obtained was 82.5 with very good criteria. sig. (2-tailed) value is 0.005 < 0.05 or t count is greater than t table, because there are ( t count 3,525 and t table 1,8125 with df 10 with alpha 0.05, which means that there is a difference which is significant, and the effect size test shows a high influence, and there is an effect of the use of manipulative learning media on the learning motivation of 5th graders at SDN 3 Gunungsari in the 2020/2021 academic year.